The Cang-Cang Dance in the Mabang Handak Wedding Tradition Becomes a Performance Dance in Kayuagung City, Ogan Komering Ilir (OKI) Regency, South Sumatra - Kurniaty, Rizki (LANGGAM: International Journal of Social Science Education, Art and Culture, 2025)
The changing function of the Cang-cang dance, which was originally included in the Mabang Handak wedding tradition, is now widely performed in various art performances and to welcome guests at weddings and invitations to tourism office activities. The problem of this research is "Why did the Cang-cang dance change in function?". This study aims to uncover and describe the formulation of the problem in the Cang-cang dance in the Mabang Handak wedding tradition as a performance dance in Kayuagung City, Komering Ilir Regency (OKI), South Sumatra. The method used in this study is a qualitative descriptive method, which is artistic (less patterned), and is called an interpretive method because the research data is more concerned with the interpretation of data found in the field. The results of this research reveal that the reworked Cang-cang dance carries a new concept with more energetic, dynamic movements and a more epic floor plan for its performance on stage. It has been completely reworked, creating a new creative dance. However, this rework retains the concept of draping a cloth/scarf around the guest (Cang-cang). Therefore, this dance is still known as the Cang-cang dance, with its function shifting to a performance dance. The results of the research obtained, it can be concluded that the Cang-cang dance, which was originally only a traditional Mabang Handak wedding dance, has been reworked with a new concept, finally becoming a performance dance with a new creative dance.